Students’ Perception in Learning English through Blended Learning - Alma Sri Andriyani; Maulina Maulina; Syarif Amin; Rahmat Nasrullah; Asdar Asdar; Andi Hamsiah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
Mobile technology plays an equal role with face-to-face interaction in the learning process in this current era. One of the most commonly utilized technologies is the use of social media integrated with the face-to-face teaching and learning as called a blended-learning. This recent study aims: (1) to investigate how the blended learning process is operated, (2) to determine students’ perceptions in learning English through blended learning. This study was an explanatory mixed-method research design using observation, questionnaire, and interview as instruments to collect data from the purposively selected 26 students. The results of this study indicated that the process of learning English through blended learning both offline (face-to-face) and online (WhatsApp application) was well-implemented. Besides, students also showed a lot of positive perceptions when learning English through blended learning utilizing social media of WhatsApp and through the face-to-face form of language learning interaction. Thus, the researchers concluded that blended learning maintains essential behavioral, cognitive, and emotional aspects in English learning.